Resistance Training Frequency Confers Greater Muscle Quality in Aged Individuals: A Brief NHANES Report. Issue 2 (1st July 2018) - Naimo, Marshall A.; Gu, Ja K.; Lilly, Christa; Kelley, George A.; Baker, Brent A.
Abstract: Aims: Sarcopenia, the age‐related decline in skeletal muscle mass, results in a loss of strength and functional capacity, which subsequently increases the risk of disease, disability frailty, and all‐cause mortality. Skeletal muscle quality (MQ), i.e., strength per unit muscle mass, is the ability of muscle to perform its functions, and evidence indicates it is a more influential variable underlying age‐related declines in muscle function than losses in muscle mass. Resistance training (RT) is known for enhancing skeletal MQ, improving health span, and reducing mortality. However, to the best of our knowledge, no studies have examined the relationship between RT frequency and MQ in an aged population. Thus, this study was designed to test the hypothesis that greater MQ in older individuals is associated with RT frequency. Methods and Results: Utilizing data from 2, 391 older adults in the National Health and Nutrition Survey (NHANES; 1999–2002), a secondary analysis of data was performed to see if an association existed between RT frequency and MQ in persons aged 55 years and older. Data were analyzed using analysis of covariance (ANCOVA) with three different models. Individuals were stratified into two groups based on how many days per week they performed RT: Insufficient (i.e., < two days per week) or sufficient (≥ two days per week). Muscle quality was calculated by taking the average peak force (Newtons) obtained from an isokinetic dynamometer and dividing it by lean mass, excluding bone mineral content (grams), obtained from dual‐energy X‐ray absorptiometry. The alpha level was set at <0.05. For persons aged 55 and over, a statistically significant association was found between sufficient RT and greater MQ in both unadjusted as well as adjusted models that accounted for various demographic, behavioral, and clinical characteristics (p<0.05 for all). However, when limited to those 65 and older, no statistically significant associations were observed between sufficient RT and greater MQ (p≥0.05 for all). When partitioned according to those 55 to 64 years of age and those 55 to 79 years, a statistically significant association was again observed (p<0.05 for all). No statistically significant associations were observed for individuals 65–79 years of age or those 80 years of age and older (p≥0.05 for all). Conclusions: Sufficient amounts of RT are associated with greater MQ in selected older individuals. A need exists for future randomized controlled trials that examine the dose‐response relationship between resistance training and MQ in older adults.